Intercultural health: the impact in the aimara women social identity - Valdebenito, Carolina; Rodríguez, Marilyn; Hidalgo, Andrea; Cárdenas, Ulises; Lolas, Fernando (Acta Bioethica, 2006)
This paper is part of a research project which tries to determine the socio cultural impact of public policies and the modernization process in the health care of the aimara ethnic group in Chile, from a cultural perspective. Its purpose is to approach to the meaning attributed by the aimara women from Colchane to the public policies related to reproductive health and how it impacts their cosmic vision. Our hypothesis is that the aimara women do not appropriate these public policies on reproductive health as proper because they do not respond to their cultural meaning about the reproductive process.